The famous fish beds of Lebanon: the Upper Cretaceous Lagerstätten of Haqel, Hjoula, Nammoura and Sahel Aalma - George, Hady; Bazzi, Mohamad; ElHossny, Tamara; Ashraf, Nida; Abi Saad, Pierre; Clements, Thomas (Journal of the Geological Society, 2024)
The fossils of the Lebanese Upper Cretaceous Lagerstätten, especially the articulated fish, are world renowned. Famous for their soft tissue preservation and highly sought after by fossil collectors, Lebanese fossils provide key information concerning the evolution of several major extant and extinct groups ofMesozoic organisms including cephalopods, crustaceans, hagfish, sharks, marine reptiles and pterosaurs. In fact, fossils from Lebanon are so exceptional that historical documentation describing them extends back to the Roman Empire. However, despite over 1600 years of knowledge of these fossils, a thorough understanding of the depositional environments, taphonomy and palaeoecology of the four main sites, Haqel, Hjoula, Nammoura (each Cenomanian in age) and Sahel Aalma (Santonian), is lacking. Here we compile a review of the palaeoenvironments, fauna and flora of these four Lebanese Lagerstätten. Our synthesis outlines the history of fossil discovery, and describes the current understanding of the geology, ages, mode of preservation and organisms found at these four sites.We also undertake a bibliometric and holotype analysis to investigate the impact that scientific colonialism has had on Lebanon. Our data confirm that local Lebanese researchers are typically not included in publications pertaining to Lebanese fossils and that the majority of Lebanese type material is stored in large historical collections outside Lebanon, predominantly in institutions within the northern hemisphere. Here, we recommend some basic practices for researchers utilizing historical collections that can help develop local Lebanese fossil collections and establish more research opportunities for local palaeontologists.
CRIS-Team Scopus Importer:2024-11-01